DYSTOCIA DUE TO DICEPHALUS MONSTOMUS MONSTER IN A CROSSBRED COW - RAO, K SADASIVA; PRAHALAD, P; Reddy, K C S; RAJU, K G S (The Indian Journal of Animal Reproduction, 2011)
A rare case of dicephalus monstomus monster is reported and the anatomical structure of the monster is discussed.
Keywords: Crossbred Cow; Dystocia; Dicephalus Monstomus monster